"Long‐hood method" for identification of the bleeding site in colonic diverticular hemorrhage. Issue 1 (18th November 2019) - Kobayashi, Katsumasa; Furumoto, Yohei; Narasaka, Toshiaki
Abstract : Watch a video of this article